Reconciling the Views of Project Success: A Multiple Stakeholder Model. Issue 5 (October 2018) - Davis, Kate
This article presents a new model encompassing all the important critical attributes needed to measure project success across different stakeholder groups. The study investigates the possibility that project failure is a result of the interpretations of the criteria and factors used for success by multiple stakeholder groups. Unique projects must have their outcome parameters monitored and controlled to minimize the chances of failure and the likely major financial and managerial ramifications for the organization. Early testing of the model supports its use to increase the shared, multiple stakeholder perception of project success, leading to more informed decision making and motivation of employees.